Peran Minat Berwirausaha, Motivasi Berwirausaha, dan Pendidikan Kewirausahaan dalam Meningkatkan Keterampilan Berwirausaha TKMP - Rahmat Junaidi; Pinkan Razita; Rosnelly Roesdi (Forum Kerjasama Pendidikan Tinggi, 2026)
Pemula (TKMP) Abstract−This research aims to determine the influence of entrepreneurial interest, entrepreneurial motivation, and entrepreneurship education on the entrepreneurial skills of Independent Beginner Workforce (TKMP) participants in Riau Province. The population in this study consists of 124 participants, with sampling conducted using the saturated sampling technique, making the entire population the research sample. Primary data were collected through interviews and questionnaires. The data analysis method employed was Multiple Linear Regression in SPSS 21. The research results indicate that entrepreneurial interest, entrepreneurial motivation, and entrepreneurship education simultaneously have a positive and significant influence on the entrepreneurial skills of Independent Beginner Workforce (TKMP) participants in Riau Province, with F-calculated value (36.579) > F-table (2.680) or significance value (0.000) < 0.05. Entrepreneurial interest has a positive and significant influence on the entrepreneurial skills of Independent Beginner Workforce (TKMP) participants in Riau Province, with t-calculated value (3.556) > t-table (1.979) or significance (0.001) < 0.05. Entrepreneurial motivation has a positive and significant influence on the entrepreneurial skills of Independent Beginner Workforce (TKMP) participants in Riau Province, with t-calculated value (4.332) > t-table (1.979) or significance (0.000) < 0.05. Entrepreneurship education has a positive and significant influence on the entrepreneurial skills of Independent Beginner Workforce (TKMP) participants in Riau Province, with t-calculated value (2.574) > t-table (1.979) or significance (0.011) < 0.05.